The effect of additives metal on the D.C conductivity of epoxy resin - Baghdad Science Journal (مجلة بغداد للعلوم)
The present studies are focused on the modification of the properties of epoxy resin with different additives namely aluminum, copper by preparing of composites systems with percentage (20%, 40% and 50%) of the above additives. The experimental results show that the D.C of conductivity on wt% filler content at ( 293-413 ) K electrical conductivity of all above composites increased with temperature for composites with filler contact and find the excellent electrical conductivity of copper and lie between (2.6*10-10 - 2.1*10-10)?.cm . The activation energy of the electrical conductivity is determined and found to decrease with increasing the filler concentration.